Makna Pluralitas Agama di Kalangan Mahasiswa STAIN Kudus dan Implementasinya Melalui Mata Kuliah Perbandingan Agama - Efa Ida Amaliyah (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2017)
This article reveals two things concerning about the religion plurality among STAIN Kudus students. The first, “what is the meaning of religion plurality from the student point of view?” The second, “how will the course give a contribution about the religion plurality for the students?” Based on the result of research among students of STAIN Kudus, expressed that the students have their own meanings and assumptions depend on their knowledge and experiences. These are: firstly, with the religious pluralism which will show that there are some differences religions surround us to be respected each other’s. Secondly, there is the attitude to respect and appreciate or to be tolerant to other religions. Thirdly, there is the belief that all religions are good, but they still believe that the best and the true one is Islam. The most of students defined the religion plurality is to respect and appreciate another people beliefs and doctrines. It was needed to avoid horizontal conflict among the people in the grass roots. The other side, the implementation of the concept of religion plurality through the comparative of religion course will give the insight to the students to make balance between theory and practices.